2019
DOI: 10.15761/aeph.1000112
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the relationship between annual airborne pollen levels during four decades of 1975–2014 and annual occurrence of ulcerative colitis, Crohn's disease, primary biliary cirrhosis, fulminant hepatitis, severe acute pancreatitis, interstitial pneumonia, amyloidosis, based on the national registry database of specific intractable diseases in Japan

Abstract: Background: Systemic vasculitis such as Kawasaki Disease (KD) and collagen diseases have been suggested to be related to pollen exposure (PE).Objective: To elucidate effects of PE on outbreaks of gastrointestinal diseases including inflammatory bowel diseases(IBDs) and associated diseases. Methods:We analyzed national database on annual occurrence of ulcerative colitis(UC), Crohn's disease(CD), as well as primary biliary cirrhosis(PBC), fulminant hepatitis(FH), severe acute pancreatitis(SAP), interstitial pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 13 publications
(26 reference statements)
3
23
0
Order By: Relevance
“…In the background, the author noted that data from the late 1980s to around 2000 showed that the number of pollen dispersed in Wuhan was by far the highest among the major cities in China [6][7][8]. The author compared the changes in the number of pollen counts observed at the National Hospital Organization Sagamihara Hospital [2][3][4]9] and Tokyo Metropolitan Government [4] from the 1970s to the 2010s with the changes in the number of cases of Kawasaki disease, 40 designated intractable diseases [10,11], and 24 types of cancer and malignant tumors [12,13]. We have found epidemiological facts that pollen exposure, which most Japanese people are inevitably exposed to for more or less eight months a year immediately after birth, is strongly associated with the development of these incurable diseases.…”
Section: Why Was Sars-cov-2 Born In Wuhan In 2019?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the background, the author noted that data from the late 1980s to around 2000 showed that the number of pollen dispersed in Wuhan was by far the highest among the major cities in China [6][7][8]. The author compared the changes in the number of pollen counts observed at the National Hospital Organization Sagamihara Hospital [2][3][4]9] and Tokyo Metropolitan Government [4] from the 1970s to the 2010s with the changes in the number of cases of Kawasaki disease, 40 designated intractable diseases [10,11], and 24 types of cancer and malignant tumors [12,13]. We have found epidemiological facts that pollen exposure, which most Japanese people are inevitably exposed to for more or less eight months a year immediately after birth, is strongly associated with the development of these incurable diseases.…”
Section: Why Was Sars-cov-2 Born In Wuhan In 2019?mentioning
confidence: 99%
“…As many as 40 designated intractable diseases are equally affected by pollen exposure, to a greater or lesser extent, and this has been verifi ed in the process of making graphs for Kawasaki disease (Figure 1), Takayasu disease, vasculitis syndromes [10], collagen diseases [10], Parkinson's disease, multiple sclerosis, ulcerative colitis [11], interstitial pneumonia [11], etc. In the process, the author was convinced that, given the commonality of life phenomena and disease pathology, cancer is also likely to be caused by pollen exposure (Figure 2) [12,13].…”
Section: Why Was Sars-cov-2 Born In Wuhan In 2019?mentioning
confidence: 99%
“…In addition to genetic predisposition, environmental factors are thought to play a role in the pathogenesis of designated incurable specific intractable diseases (SIDs) and cancer and malignant tumors, and the possibility of microorganisms [1][2][3][4] and pollen [5][6][7][8][9][10] as candidate environmental factors has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the author found that the trigger for Takayasu disease, a designated incurable specific intractable diseases (SIDs), which is a vasculitis syndrome like Kawasaki disease, may also be caused by pollen, and the author has continued to report his opinion that the trigger for not only Kawasaki disease but also 40 designated intractable diseases and 24 types of cancer and malignant tumors may be pollen [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation